The Association of Osteosarcopenia With Functional Disability in Community-Dwelling Mexican Adults 50 and Older - López-Teros, Miriam T.; Rosas-Carrasco, Oscar; Sánchez-García, Sergio; Castro-Porras, Lilia; Luna-López, Armando; Agudelo-Botero, Marcela (Frontiers in Medicine, 2021)
Background: Osteosarcopenia (OS) associate with functional disability (DF) in older people, early evaluation of these geriatric conditions could help prevent DF and thereby contribute to improving the quality of life of older people. Objective: To analyze the association between OS with functional FD in adults 50 years and older living in community. Design: Cross-sectional analysis of the Frailty, Dinapenia and Sarcopenia Study in Mexican Adults (FraDySMex). Setting and Participants: 825 people were included, 77.1% women, aged 70.3 ± 10.8 years. Methods: The OS was defined when the person was diagnosed with Sarcopenia (SP) plus osteoporosis, the SP diagnosis was evaluated in accordance with the criteria of the European Working Group for the Definition and Diagnosis of Sarcopenia (EWGSOP), and osteoporosis using the World Health Organization (WHO) criteria. Muscle mass and bone mass were evaluated using dual-energy X-ray absorptiometry (DXA). The FD was evaluated using the basic activities of daily living (BADL) and the instrumental activities of daily living (IADL). Additionally, other sociodemographic and health variables such as sex, age, schooling, cognitive status, depression, comorbidity, hospitalization, polypharmacy, urinary incontinence, and nutrition variables such as risk of malnutrition and obesity were included. Associations between OS with DF were evaluated using multiple logistic regression. Results: The average age was 70.3±10.8 years and 77.1% were women. The prevalence of OS and FD and OS was 8.9% and 8.9%, respectively. The OS is associated with significant FD [OR: 1.92; CI 95% 1.11-3.33]. Conclusions and Implications: Early evaluation of geriatric conditions associated with changes in body composition such as OS could help clinical staff prevent DF and thereby contribute to improving the quality of life of older people.